If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 7(2c + -6) Reorder the terms: 10 = 7(-6 + 2c) 10 = (-6 * 7 + 2c * 7) 10 = (-42 + 14c) Solving 10 = -42 + 14c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-14c' to each side of the equation. 10 + -14c = -42 + 14c + -14c Combine like terms: 14c + -14c = 0 10 + -14c = -42 + 0 10 + -14c = -42 Add '-10' to each side of the equation. 10 + -10 + -14c = -42 + -10 Combine like terms: 10 + -10 = 0 0 + -14c = -42 + -10 -14c = -42 + -10 Combine like terms: -42 + -10 = -52 -14c = -52 Divide each side by '-14'. c = 3.714285714 Simplifying c = 3.714285714
| 2z^2=200 | | -3m+1=16 | | 8+4(3w-2)=-2(4w-5)+2w | | -3m+1=-16 | | 15x^2-1=0 | | 12=3y+4y-y | | 2+j=-14 | | -7m+m=-6 | | -6x+2(5)=20 | | 5+2(x-3)=13 | | 4p-12=4p-24 | | (s^2-2s+1)(s^2-6s+9)=0 | | -8x+8x=0 | | 4n+5=7-n-2+5n | | 8+4(-5y-2)=-140 | | 8x+18x= | | 2x+4+2x=2x+3 | | 16d-7d=-3d+2 | | 4+z(2z+3)=15 | | -18-5=2m | | 5.5(x-3)=-0.5x+13.5 | | .5n+3=21 | | 33x+1=34x-2 | | 3x+8-5x=30 | | -12-5=2m | | -6g-15=-3(2g+5) | | 6x+9=7x+11 | | 10=2x+3y | | -6-5=2m | | -13=1+3x-2 | | 6x=64+6x | | 8c+2=8+5c |